Corporate governance and financial restatements. - Koh, Jean Pei Chen. (2008)
This study sought to investigate the association between corporate governance and auditor independence with financial restatements using a sample of 78 restating firms which restated for fiscal year 2001 matched with 78 non-restating firms.